A Highly Nonlinear Spiral Photonic Crystal Fiber for Tailoring Two Zero Dispersion Wavelengths in the Visible Region - Hossain, Muhammad Nazmul; Alam, M. Shah; Hasan, Dihan Md. Nuruddin; Mohsin, K. M. (Photonics Letters of Poland, 2010)
A dispersion flattened, spiral silica photonic crystal fiber (SSPCF) is presented here for supercontinuum generation in the visible region. Two zero dispersion wavelengths (ZDWs) (570nm & 630nm) are obtained in the visible region for a core diameter of 600nm and the range of the anomalous dispersion increasing with the increment of the core diameter. The fiber shows high nonlinearity parameter (1433W-1km-1), high Raman gain (698.478W-1km-1), ultraflattened dispersion (-0.05064 ps/nm2.km) and very low confinement loss (0.00161 dB/km) at 600 nm. The proposed SSPCF shows improvement over the dispersion control of a hexagonal PCF, and low damage threshold of a highly nonlinear (HN) soft glass PCF. So it can be an excellent candidate for generating supercontinuum in the visible region with HeNe laser of pump wavelenght at 612nm. Full Text: PDF References: J. K. Ranka, R. S. Windeler, and A. J. Stentz, Opt. Lett. 25, 25 (2000), http://www.opticsinfobase.org/ol/abstract.cfm?uri=ol-25-1-25 [CrossRef] J. M. Dudley, G. Genty, and S. Coen, Rev. Mod. Phys.78, 1135 (2006). [CrossRef] A. Kudlinski, G. Bouwmans, M. Douay, M. Taki, and A. Mussot, J. Lightwave Technol. 27, 1556 (2009). [CrossRef] A. Agrawal, N. Kejalakshmy, J. Chen, B. M. A. Rahman, and K. T. V. Grattan, Opt. Lett. 33, 2716 (2008), http://www.opticsinfobase.org/ol/abstract.cfm?uri=ol-33-22-2716. [CrossRef] A. Agrawal, N. Kejalakshmy, J. Chen, B. M. A. Rahman, and K. T. V. Grattan, IEEE Photon. Technol. Lett. 21, 1722 (2009). [CrossRef] C. Seaton and J. Clowes, Opt. Eng. 20, 19 (2009), http://www.opticsinobase.org/OPN/abstract.cfm?uri=OPN-20-12-19 [CrossRef] J. Cascante Vindas, S. Torres Peiró, A. Diez M. V. Andrés, Appl. Phys. 3723 (2009). COMSOL Multiphysics, version 3.2, 2005. L. An, Z. Zheng, Z. Li, Y. Liu, T. Zhou, and J. Cheng, Asia Communications and Photonics Conference and Exhibition, ThA4, http://www.opticsinfobase.org/abstract.cfm?uri=ACP-2009- ThA4 K. Saitoh, N. Florous, and M. Koshiba, Opt. Exp. 13, 8365 (2005), http://www.opticsinfobase.org/oe/viewmedia.cfm?uri=oe-13-21-8365&seq=0 K. Saitoh, M. Koshiba, T. Hasegawa, E. Sasaoka, Opt. Exp. 11, 843 (2003). http://www.opticsinfobase.org/abstract.cfm?id=71986 R. T. Bise, D. Trevor, Opt. Fiber Communication Conference 3, 3 (2005), http://www.opticsinfobase.org/abstract.cfm?uri=OFC-2005-OWL6 S.G. Leon-Saval, T.A. Birks, W.J. Wadsworth, P.St.J. Russell, Opt. Exp. 12, 2864 (2004) http://www.opticsinfobase.org/oe/abstract.cfm?id=80305 C. K. F. Ho, K. Pita, N.Q. Ngo, and C.H. Kam, Opt. Exp. 13, 1049 (2005), http://www.opticsinfobase.org/oe/abstract.cfm?URI=OPEX-13-3-1049 S. Roy, K. Mondal, and P. Roy Chaudhuri, Appl. Opt. 48, G106, (2009), http://www.opticsinfobase.org/abstract.cfm?uri=ao-48-31-G106 [CrossRef] T. Sun, G. Kai, Z. Wang, S. Yuan, and X. Dong, Chinese Opt. Lett. 6, 93 (2008). [CrossRef] J. Bromage, K. Rottwitt, and M. E. Lines, IEEE Photon. Technol. Lett. 14, 24 (2002) [CrossRef]